PERKAWINAN YANG TIDAK DICATATKAN: DAMPAKNYA BAGI ANAK - Joni, Muhammad (Sunan Kalijaga State Islamic University & The Asia Foundation, 2013)
The analysis in this article will utilize the principles of non-discrimination and the best interest of the child. The principle of non -discrimination is central in all international human rights convention. This principle of non-discrimination is deeply entwined with the principle of the best interest of the child. The latter principle is of paramount consideration in the issue of marriage registration. This article stresses that registration of marriage is not simply a simple nor personal issue, but also raises the issue of the rights of children. Therefore, this issue cannot be distanced from the responsibility and role of the state. Unregistered marriages have a direct effect on children as legal subjects, and individual whose rights are guaranteed, recognized and protected. Unregistered marriages are simply incompatible with the rights of children, as those marriages are positioned vis-à-vis the need for child protection, whether in family law or their individual fulfillment of rights. The legal consequence from such unregistered marriages is unfairly burdened on children. Therefore, the risks and consequences of such marriages stand as a barrier to children’s rights. The legal vacuum which arise must be dealt with. Children born from unregistered marriages must still have a legal relationship with both parents, a relationship which cannot be subverted legally. Even when born from unregistered marriages, the non-marital child must still have civil relations with his biological mother and her kin as well as his biological father and his kin.